2001
DOI: 10.1258/1355819011927486
|View full text |Cite
|
Sign up to set email alerts
|

Motives for seeking a second opinion in orthopaedic surgery

Abstract: Patients did not seek a second opinion because they had doubts about the competence of their treating consultant, but because they were dissatisfied about the level of communication or about the results of their treatment. Medical educators should continue to increase their efforts to improve specialists' communication and relationship skills since these seem to generate referrals for second opinions, which occupy clinic space that could be used by other patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…Patients may even fear negative repercussions in terms of their subsequent care if they were to raise such concerns. Orthopaedic surgeons might do well to consider the potential ramifications associated with concerns of this nature; for example, recent work from The Netherlands showed that 30% of new patients visiting an orthopaedic surgical outpatient clinic were seeking a second opinion 17 and that these patients were often motivated not by doubts about the competency of the treating consultant but by a lack of trust in, or dissatisfaction with, the consultant who provided the first opinion. Because the number of secondopinion consultations in orthopaedic surgery is increasing rapidly 18,19 , it is important to consider the patients' motivations for seeking them.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may even fear negative repercussions in terms of their subsequent care if they were to raise such concerns. Orthopaedic surgeons might do well to consider the potential ramifications associated with concerns of this nature; for example, recent work from The Netherlands showed that 30% of new patients visiting an orthopaedic surgical outpatient clinic were seeking a second opinion 17 and that these patients were often motivated not by doubts about the competency of the treating consultant but by a lack of trust in, or dissatisfaction with, the consultant who provided the first opinion. Because the number of secondopinion consultations in orthopaedic surgery is increasing rapidly 18,19 , it is important to consider the patients' motivations for seeking them.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of oncologists evaluate monthly between 1 and 5 patients for second opinions and roughly one third of patients with advanced cancer seek the second medical opinion, to improve at least patient-physician communication, enhanced information, and reassurance [42,[45][46][47].…”
Section: Second Medical Opinion Network In Oncologymentioning
confidence: 99%
“…Concern over the competence of the treating specialist is usually not the reason for seeking a second opinion. One study has indicated that the best predictor for a patient seeking a second opinion lies in the patient's relationship with their first-opinion consultant [9]. First-opinion consultants are often not aware of communication issues [9].…”
Section: Referencesmentioning
confidence: 99%
“…One study has indicated that the best predictor for a patient seeking a second opinion lies in the patient's relationship with their first-opinion consultant [9]. First-opinion consultants are often not aware of communication issues [9]. Other studies have addressed the legal and ethical issues involved [7,10].…”
Section: Referencesmentioning
confidence: 99%